2017
DOI: 10.3389/fpls.2017.01115
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Response of Purple Willow (Salix purpurea) to Arsenic Stress

Abstract: Arsenic (As) is a toxic element for plants and one of the most common anthropogenic pollutants found at contaminated sites. Despite its severe effects on plant metabolism, several species can accumulate substantial amounts of arsenic and endure the associated stress. However, the genetic mechanisms involved in arsenic tolerance remains obscure in many model plant species used for land decontamination (phytoremediation), including willows. The present study assesses the potential of Salix purpurea cv. ‘Fish Cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 94 publications
2
15
0
Order By: Relevance
“…Each of the arsenic concentrations applied to the water mimosas had significant detrimental effects on the plants' growth and development. These results are in parallel with reports on other high-tolerance species such as Salix purpurea (Purple willow) [45], Pteris vittata (Chinese brake) [46], Oryza sativa (rice) [47], and Typha latifolia [48]. It has been shown that severe concentration of arsenic dosages inhibited the normal life cycle of plants and in the detrimental phase, could kill plants.…”
Section: Macromorphological Observation Of Water Mimosa Under Differesupporting
confidence: 87%
See 2 more Smart Citations
“…Each of the arsenic concentrations applied to the water mimosas had significant detrimental effects on the plants' growth and development. These results are in parallel with reports on other high-tolerance species such as Salix purpurea (Purple willow) [45], Pteris vittata (Chinese brake) [46], Oryza sativa (rice) [47], and Typha latifolia [48]. It has been shown that severe concentration of arsenic dosages inhibited the normal life cycle of plants and in the detrimental phase, could kill plants.…”
Section: Macromorphological Observation Of Water Mimosa Under Differesupporting
confidence: 87%
“…However, this plant also showed general plant dysfunction at high concentrations. The same results were achieved in a study on purple willow (Salix purpurea) under 30 and 100 ppm arsenic concentrations [45]. Interestingly, water hyacinths treated with 70 and 100 ppm arsenic showed the same absorption of foliar-applied arsenic with the arsenic hyper-accumulating fern (Pteris vittata L.) [78].…”
Section: Arsenic Accumulation Of Water Mimosasupporting
confidence: 77%
See 1 more Smart Citation
“…Inorganic arsenite (As(III)) and arsenate (As(V)) are the dominant forms in water and soil. As(V) is the major form in aerobic conditions, whereas As(III) is the most abundant under a reducing environment (Yanitch et al 2017 ). Inorganic As can be converted in plants to two organic forms (monomethylarsonic acid (MMA) and dimethylarsinic acid (DMA)) present in extensive amounts (Mishra et al 2017 ; Zhu et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high survivability and easy adaptation of trees, undisturbed growth, and effective phytoextraction of toxic elements/metalloids make them highly suitable for remediation of substrates polluted by As forms. The chemical structure of As(V) is similar to phosphorus (P); therefore, it can be easily incorporated through phosphate (Pi) transporters into plants (Yanitch et al 2017 ). As(III) is similar to sulfur (S), which is uptaken from substrate by nodulin26-like intrinsic aquaporin channels (NIPs) and bounds to the sulfhydryl groups of peptides and proteins inhibiting their activity (Mishra et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%